Review about José Ramón López Bausela: The blue school of Falange Española de las J.O.N.S. A fascist project dismantled by implosion - Ramírez Aísa, Elías (Avances en Supervisión Educativa, 2017)
Review of the book by José Ramón López de Bausela: The blue school of the Spanish Falange of the J.O.N.S. A fascist project dismantled by implosion. Spanish Fascism during the Second Republic, articulated through a political organization called the Spanish Falange de las JONS, was the result of the union of several previous organizations that merged in 1934, remaining as an autonomous political group until April 1937, date of the creation of Traditionalist Spanish Falange and of the JONS, moment in which all the insurgent political forces were united and they finished with the campaigning State, according to the saying of a high leader. Well, the period between these two dates, in the field of education, is the object of analysis of the book of the teacher and inspector of education José Ramón López Bausela. That Spanish Falange that defended a concept of nation or country based on an indoctrinating and immobile past about the rhetoric of the Empire, founder of an ethic and a tradition, all hindered by ideals of service, seasoned, and this is perhaps the novelty that contributes Spanish fascism, for the defense of Catholicism, is the background of the content of this book. This fascism, which in turn advocates corporate harmony, played a prominent role, before and during the civil war as a critic of the republican educational culture and worldview. This is: this is a book that analyzes the relationship of the Spanish Falange with education, with the school.